Interplay of host specificity and biogeography in the population structure of a cosmopolitan endoparasite: microsatellite study of Ligula intestinalis (Cestoda) - Stefka, J; Hypsa, V; Scholz, T (Molecular ecology, 2009)
Organisms with wide geographical or phenotypic diversity often constitute assemblages of genetically distinct species or lineages. Within parasites, an emergence of host-specific lineages is assumed to create such cryptic variability; however, empirical evaluation of these processes is scarce. Here, we analyse populations of a parasite with a complex life cycle, wide host spectrum and global distribution, with the aim to reveal factors underlying the evolution of host- or geography-dependent lineages. Using 15 microsatellite loci, deep genetic distances were observed between populations from distant geographical areas. On the local scale, host-mediated genetic structure was found among sympatric samples. Two lineages differing in the spectrum of infected hosts co-occurred in the Euro-Mediterranean area, and two distinct lineages were recovered from Lake Tana in Ethiopia. Although sampled across several host taxa and multiple localities, a lack of marked genetic structure was seen in the populations belonging to one of the European lineages. Only weak genetic differentiation between sympatric samples from two host species was found. Complexity of the parasite life-cycle contributed to such a stratified pattern. Differences in the immune response between fish hosts were suggested as the factor diversifying the populations locally; conversely, high mobility of the parasite due to migration with its bird (definitive) host were assessed to homogenize populations across the area of distribution. However, despite the high mobility, large bodies of salt water prevent the parasite from long-distance migrations, as was demonstrated in an example of the Mediterranean Sea which represented an effective barrier to gene flow.
Keywords: Ethiopia; Mediterranean Sea; zeměpis; ptáci; Birds; tok genů; populační genetika; druhová specificita; ryby; Sequence Analysis, DNA; Geography; Genetics, Population; Microsatellite Repeats; Gene Flow; Host-Parasite Interactions; Středozemní moře; zvířata; Etiopie; sekvenční analýza DNA; Fishes; Species Specificity; mikrosatelitní repetice; Animals; interakce hostitele a parazita; Cestoda